Pertumbuhan Mencit (Mus musculus L) Setelah Pemberian Biji Jarak Pagar (Jatropha curcas) - Muliani, Hirawati - (Bioma : Berkala Ilmiah Biologi, 2011)
The research of white mouse growth exposed to barbados nut’s seed is aimed to know about the effect ofbarbados nut’s seed on the growth of female white mouse.Thirty two female white mouse were acclimated during 1 week and then alloted into 2 groups, each groupwas treated as follows : P0 (control): were giving of aquadest; P1: were giving of 0,2 grams barbados nut’s seedpowder daily per mouse. Barbados nut’s seed powder were given by pipet to the mouth of the mouse. Long of thetreatment was 14 days and each treatments with 16 replication.Main parameter observed was the change of the body weight. Supporting parameter was the foodconsumption. Data was analyzed by varians analysis with Completely Random Design.The white mouse was exposed of the barbados nut’s seed decrease of the body weight.